Human Papillomavirus Type 16 E7 oncoprotein engages but does not abrogate the mitotic spindle assembly checkpoint - Yu, Yueyang (2012)
The mitotic spindle assembly checkpoint (SAC) ensures faithful chromosome segregation during mitosis by censoring kinetochore-microtubule interactions. It is frequently rendered dysfunctional during carcinogenesis causing chromosome missegregation and genomic instability. There are conflicting reports whether the HPV16 E7 oncoprotein drives chromosomal instability by abolishing the SAC. Here we report that degradation of mitotic cyclins is impaired in cells with HPV16 E7 expression. RNAi-mediated depletion of Mad2 or BubR1 indicated the involvement of the SAC, suggesting that HPV16 E7 expression causes sustained SAC engagement. Mutational analyses revealed that HPV16 E7 sequences that are necessary for retinoblastoma tumor suppressor protein binding as well as sequences previously implicated in binding the Nuclear and Mitotic Apparatus (NuMA) protein and in delocalizing dynein from the mitotic spindle contribute to SAC engagement. Importantly, however, HPV16 E7 does not markedly compromise the SAC response to microtubule poisons.